Kynurenine pathway, NAD+ synthesis, and mitochondrial function: Targeting tryptophan metabolism to promote longevity and healthspan - Castro-Portuguez, Raul; Sutphin, George L. (Experimental gerontology, 2020)
Aging is characterized by a progressive decline in the normal physiological functions of an organism, ultimately leading to mortality. Nicotinamide adenine dinucleotide (NAD+) is an essential cofactor that plays a critical role in mitochondrial energy production as well as many enzymatic redox reactions. Age-associated decline in NAD+ is implicated as a driving factor in several categories of age-associated disease, including metabolic and neurodegenerative disease, as well as deficiency in the mechanisms of cellular defense against oxidative stress. The kynurenine metabolic pathway is the sole de novo NAD+ biosynthetic pathway, generating NAD+ from ingested tryptophan. Altered kynurenine pathway activity is associated with both aging and a variety of age-associated diseases. Kynurenine pathway interventions can extend lifespan in both fruit flies and nematodes, and altered NAD+ metabolism represents one potential mediating mechanism. Recent studies demonstrate that supplementation with NAD+ or NAD+-precursors increase longevity and promote healthy aging in fruit flies, nematodes, and mice. NAD+ levels and the intrinsic relationship to mitochondrial function have been widely studied in the context of aging. Mitochondrial function and dynamics have both been implicated in longevity determination in a range of organisms from yeast to humans, at least in part due to their intimate link to regulating an organism's cellular energy economy and capacity to resist oxidative stress. Recent findings support the idea that complex communication between the mitochondria and the nucleus orchestrates a series of events and stress responses involving mitophagy, mitochondrial number, mitochondrial unfolded protein response (UPRmt), and mitochondria fission and fusion events. In this review, we discuss how mitochondrial morphological changes and dynamics operate during aging, and how altered metabolism of tryptophan to NAD+ through the kynurenine pathway interacts with these processes. [Display omitted] •The kynurenine pathway has recently been identified as a promising target to increase healthy longevity.•Targeted inhibition of kynurenine pathway activity may alleviate several pathological conditions and promote healthspan.•Altered production and recycling of NAD+ is a likely mediator of the beneficial effects of kynurenine pathway interventions.•NAD+-dependent changes to mitochondrial function and dynamics may mediate the benefits of altered kynurenine metabolism.